2013
DOI: 10.1021/es3022073
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phytase from Pteris vittata Resistant to Arsenate, High Temperature, and Soil Deactivation

Abstract: Arsenate interferes with enzymatic processes and inhibits inorganic phosphorus (Pi) uptake in many plants. This study examined the role of phytase and phosphatase in arsenate tolerance and phosphorus (P) acquisition in the arsenic hyperaccumulator Pteris vittata . Enzyme-mediated hydrolysis of phytate in P. vittata extracts was not inhibited by arsenate at 5 mM or by heating at 100 °C for 10 min. Root exudates of P. vittata exhibited the highest phytase activity (18 nmol Pi mg(-1) protein min(-1)) when availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(80 citation statements)
references
References 44 publications
(91 reference statements)
10
70
0
Order By: Relevance
“…However, this was not the case for phytate-P. It is reported that PV roots secrete phytase, which is the only enzyme that hydrolyzes phytate to inorganic P (Lessl et al, 2013). Moreover, enzyme-mediated hydrolysis of phytate in PV root extracts is not inhibited by 0.5e5 mM AsV (Lessl et al, 2013).…”
Section: P Vittata Grew Better On Media Amended With Arsenic and Phymentioning
confidence: 96%
See 4 more Smart Citations
“…However, this was not the case for phytate-P. It is reported that PV roots secrete phytase, which is the only enzyme that hydrolyzes phytate to inorganic P (Lessl et al, 2013). Moreover, enzyme-mediated hydrolysis of phytate in PV root extracts is not inhibited by 0.5e5 mM AsV (Lessl et al, 2013).…”
Section: P Vittata Grew Better On Media Amended With Arsenic and Phymentioning
confidence: 96%
“…Their spores were first sterilized with 75% alcohol for 2 min and rinsed three times with sterile deionized (DI) water, then surface sterilized in a 10% sodium hypochlorite for 12 min and rinsed thoroughly with sterile DI water before being sown in Petri dishes with solid medium Lessl et al, 2013 (Mathews et al, 2010). Spores were suspended in 2 mL sterile DI water and uniformly dispersed on agar in sterile Petri dishes (100 mm  13 mm; 500 mL per plate).…”
Section: Spores Sterilization and Gametophyte Culturementioning
confidence: 99%
See 3 more Smart Citations